1996
DOI: 10.1007/bf00016175
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition of Photosystem I electron transfer activity in isolated Photosystem I preparations with different chlorophyll contents

Abstract: Photoinhibition of the light-induced Photosystem I (PS I) electron transfer activity from the reduced dichlorophenol indophenol to methyl viologen was studied. PS I preparations with Chl/P700 ratios of about 180 (PS I-180), 100 (PS I-100) and 40 (PS I(HA)-40) were isolated from spinach thylakoid membranes by the treatments with Triton X-100, followed by sucrose density gradient centrifugation and hydroxylapatite column chromatography. White light irradiation (1.1 × 10(4)μE m(-2) s(-1)) of PS I-180 for 2 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 42 publications
2
58
1
Order By: Relevance
“…In each case, it was observed when chilling-sensitive plants were exposed to a combination of light stress and chilling stress, and the effect could be prevented by a blockage of linear electron transport. With chloroplast fragments, photoinactivation of PS I has also been observed in the absence of chilling stress (Satoh 1970a, b;Sonoike 1995;Baba et al 1996). Our observation of PS I inactivation at room temperature (Table 1 and Herrmann et al 1995) demonstrates that chilling stress is not a basic requirement for this phenomenon (Sonoike 1996).…”
Section: Discussionsupporting
confidence: 49%
“…In each case, it was observed when chilling-sensitive plants were exposed to a combination of light stress and chilling stress, and the effect could be prevented by a blockage of linear electron transport. With chloroplast fragments, photoinactivation of PS I has also been observed in the absence of chilling stress (Satoh 1970a, b;Sonoike 1995;Baba et al 1996). Our observation of PS I inactivation at room temperature (Table 1 and Herrmann et al 1995) demonstrates that chilling stress is not a basic requirement for this phenomenon (Sonoike 1996).…”
Section: Discussionsupporting
confidence: 49%
“…This is a heterodimer to which the majority of the core antenna pigments, as well as most of the reaction center cofactors, are bound. In PSI core preparations, strong light exposure induced changes to both reaction‐center proteins [14]. In the present study using submembrane fractions, PsaB was more sensitive to strong light and also produced degradation products (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Also, these authors observed that under these conditions toxic hydroxyl radicals were generated. Inactivation of PSI‐mediated electron flow was also reported in isolated PSI core particles such as spinach PSI‐180 and PSI‐100, as well as cyanobacterial PSI membranes exposed to strong light [14]. In PSI core particles illuminated with strong light, damage to the light‐harvesting complex (LHC) and degradation of reaction‐center proteins as well as acceptor side proteins were observed [15].…”
mentioning
confidence: 99%
“…The PSI suspension in 200 mM phosphate buffer pH 7, containing 1 mM Triton X-100 was stored at À80°C [19]. The extract contained PSI with approximately 40 chlorophyll molecules per P700 center which was characterized for chlorophyll concentration using 80% acetone [20] while the P700 concentration was determined by monitoring the chemically induced absorbance change (recording oxidized minus reduced spectra) as described by Baba et al [6,21].…”
Section: Photosystem I Extraction and Characterizationmentioning
confidence: 99%